Performance security of the transportation system in the face of rising fuel prices - Гончаренко, А.В. (Proceedings of National Aviation University (archive), 2009)
Expectation of a transport system operational costs, for a determined time interval, as an index of its safety functioning, in conditions of fuel prices growth, is considered. Attention is paid to the influence of unexpected loses due to crash events. Achieved results of applicable researches. Plotted appropriate diagrams.